Relevansi antara Nilai Pendidikan dalam Cerita Rakyat Golan Mirah dengan Pitutur Jawa serta Implemetasinya di Era 4.0: - - Istanti Fatkhul Janah (Journal of Education and Learning Sciences, 2021)
Ponorogo as a cultural city in East Java, besides being famous for Reyog, Ponorogo also has a wealth of local wisdom. One of the local wisdoms that is well-known in the wider community and until now the tradition in it is still very rich, namely the folklore of Golan Mirah. This folklore has noble educational values ​​that are relevant to Javanese speech. The purpose of this study is to identify and analyze educational values ​​in the Golan Mirah folklore and their relevance to Javanese poetry and its implementation in this 4.0 era. The method used is descriptive qualitative research. The results of this study are the relevance of the educational value in the folklore of Golan Mirah and Pitutur Jawa, namely 1) Anak polah Bapa kepradah; 2) Adigang, adigung, adiguna; 3) Sura dira jayaningrat, lebur dening pangastuti; dan 4) Desa mawa cara negara mawa tata. In addition, how to implement the relevance in this 4.0 era.